NARRATIVE, MEANING, AND DISASTER AWARENESS: A DISCOURSE-PRAGMATIC ANALYSIS OF THE CUPU PANJALA TRADITION IN MEGATHRUST MITIGATION - Rohmah, Anindi Nur; Wulandari, Yosi; Ekici, Gail (Journal of Pragmatics and Discourse Research, 2026)
Communities living in megathrust-prone regions of Indonesia continue to face recurring seismic and hydrometeorological hazards, yet disaster communication often remains limited to technical or institutional channels. This gap leaves many rural populations dependent on cultural knowledge systems to interpret environmental uncertainty. The Cupu Panjala tradition in Padukuhan Mendak, Gunungkidul, represents one such indigenous mechanism, functioning as a ritualized narrative that encodes warnings, environmental memory, and moral regulation. This study aims to examine the Cupu Panjala tradition as a communicative system of local disaster awareness rather than a static myth or folklore. Using a qualitative approach grounded in discourse-pragmatic analysis, data were collected through oral narratives, ritual performances, and community interpretations associated with the Cupu Panjala ceremony. The analysis focuses on how narrative structures, symbolic references, and communicative intentions shape collective perceptions of natural hazards. Findings indicate that the symbolic messages within the Cupu Panjala tradition, such as references to red soil, elephants, or flowing water, serve as semiotic instruments that guide social behavior and environmental vigilance. These symbols are interpreted communally and transformed into collective awareness and preparedness actions, demonstrating that Cupu Panjala operates as a culture-based early warning system. The study concludes that the mythopoetic and pragmatic dimensions of Cupu Panjala actively reinforce social cohesion, ecological ethics, and psychological resilience. By framing disasters as communicative and moral events, the tradition contributes to community-based mitigation. Integrating such indigenous narrative systems into contemporary disaster communication can enhance culturally grounded preparedness and strengthen participatory risk management.